The Study of the Onset of Flow Boiling in Minichannels: Time-Dependent Heat Transfer Results. Issue 3 (31st December 2021) - Maciejewska, Beata; Piasecka, Magdalena; Piasecki, Artur
Abstract: The paper describes the results of boiling heat transfer during FC-72 flow in minichannels, obtained on the basis of time-dependent experiments. The main goal of the work was to determine the heat transfer coefficient by means of the finite element method with the spacetime Trefftz-type basis functions based on the Hermite interpolation. The crucial part of the experimental stand was the test section with minichannels of 1.7 mm depth. One wall of the minichannels constituted a heated foil which was resistive heated. Temperature of outer foil surface was measured due to thermocouples in the test minichannel. The onset of flow boiling was induced by two ways: lowering the pressure in the circulating system or increasing the heat flux supplied to the heater. Dynamic changes in thermal and flow experimental parameters accompanying the onset of flow boiling, including: temperature of the heater, pressure and mass flow rate, were illustrated. The results were performed as: foil temperature and heat transfer coefficient versus the distance from the minichannel inlet or time. It was observed that heat transfer coefficient values increased at the boiling incipience region for both analyzed experiments. Boiling curves were discussed. The error analysis of the results was provided. Mean relative errors of the heat transfer coefficient did not exceed 11%. Our results were compared with selected correlations from the literature.